The Concept of Enlightenment According to the Buddhist Wheel of Life - Lamirin Lamirin; Junaidi Junaidi; Haudi Haudi (Budapest International Research and Critics University, 2021)
This paper aims to answer the question: what is the concept of enlightenment according to the Buddhist wheel of life, also known as Bhavacakra. The very aim of Buddhism is to attain Nirvana, not a temporary rebirth in happy realms such as heaven or gods. There are few ways to understand enlightenment (bodhi) and several levels according to either Pali scripture. The Sanskrit scripture represents by the Tibetan and Chinese scripture also given a various range of interpretation. In order to have a broader view then it will be logical to look at those sources. Buddhists aim to attain the highest happiness that is Nirvana. Buddha himself and many teachers have laid down so many methods for us. Our ancestor teachers such as Nagarjuna, Aryadeva, and Buddhaghosa also gave many significant commentaries on this matter, especially those recorded in the Buddhist Wheel of life, teaching the twelve interdependent links.